Redescription and designation of a neotype for Ophiothrix angulata (Say, 1825 (Echinodermata: Ophiuroidea: Ophiotrichidae) - Santana, Alisson; Manso, Cynthia L.c.; Almeida, Ana C.s.; Alves, Orane F.s. (Zootaxa, 2017)
Ophiotrichidae Ljungman, 1867 comprises brittle stars diagnosed by the absence of oral papillae and presence of a cluster of dental papillae covering at least half the height of the dental plate. Ophiothrix Müller & Troschel, 1840 is the largest genus in the family and is composed of many species with a highly variable morphology. Ophiothrix angulata is one species with descriptions showing morphological variation in many of the diagnostic characters stated by Say (1825) in the original description. Say’s (1825) type material and specimens studied by him could be located. Thus, in order to elucidate the taxonomic identity of O. angulata and following Article 75 of the International Code for Zoological Nomenclature, here we propose the neotype designation of O. angulata based on topotype specimens from South Carolina, United States. A discussion of the records of O. angulata from the Atlantic Ocean is included. Taxonomic comments on the genus Ophiothrix are also provided.